Anti-Inflammatory and Anti-Angiogenesis Effects of Verapamil on Rat Air Pouch Inflammation Model - Tahereh Eteraf-Oskouei; Sevda Mikaily Mirak; Moslem Najafi (Tabriz University of Medical Sciences, 2017)
Purpose: In the present study, the effects of verapamil on inflammation and angiogenesis in air pouch model were studied. Methods: To create a model of inflammation in the rats, on days 1 and 3 sterile air, and on the sixth day, carrageenan was injected into the pouch subcutaneously. Normal saline as control, diclofenac sodium and dexamethasone as standards and verapamil (0.05, 0.1 and 0.2mg/rat) was injected into the pouch simultaneously with carrageenan and as well as 24 and 48 hours later. After 72 hours, volume of exudate, the leukocytes count, concentration of VEGF and IL-1ß, granulomatous tissue weight, histopathological changes and angiogenesis were considered. Results: Verapamil significantly reduced leukocyte accumulation in all doses, but effect of 0.1mg/rat was more significant (P<0.001). The exudate volume and granulomatous tissue weight was reduced with all doses, especially 0.1mg/rat (P<0.01). Doses 0.05, 0.1 and 0.2mg/rat of verapamil compared with the control group (carrageenan) led to a reduction in the amount of hemoglobin in the tissue as the angiogenesis indicator (P<0.001, P<0.01 and P<0.05, respectively). VEGF level of exudate was reduced by doses of 0.05 and 0.1mg/rat (P<0.05). In addition, IL-1β concentration was lowered by 0.1mg/rat of verapamil (P<0.05). Histopathological changes, severity of granulomatous inflammation, granulomatous tissue cell density and angiogenesis in verapamil group were markedly lower compared to carrageenan group. Conclusion: Verapamil has significant anti-inflammatory and anti-angiogenesis effects in the air pouch model probably due to attenuation effects of verapamil on IL-1β and VEGF.